SUPPLENESS OPTIMIZATION IN CHILDREN AGED 10-11 YEARS BY DANCE SPECIFIC ELEMENTS - Aida Petrea; Elena Rață (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this study, a series of elements both from the classical ballet (study at the barre and in the middle of the hall, jumps, etc. ) and from dance sport were chosen (cha-cha steps combinations, slow waltz, tango, etc.), that we considered to be most effective for the suppleness optimization in children aged 10-11 years. The aim of this study was to harness the motor, technical-tactical, psychical and attitudinal potential. In addition to posture, grace and the knowledge already acquired in the art of dance, the suppleness optimization represented an important criterion in the choice of future choreographies and dance genres in this group.